Work Enthusiasm in Supporting Employee Productivity (A Literature Review) - Marzuki; Chaidir; Afrizal; Akmal; Dedi Sufriadi (Universitas Serambi Mekkah, 2024)
Work enthusiasm is one of the dominant factors influencing the level of work productivity. Factors affecting work enthusiasm include the level of work motivation, work intensity, work stress, work environment, compensation, leadership style, and other variables. This research aims to explore the relationship between work enthusiasm and the level of work motivation, work intensity, work stress, work environment, compensation, and leadership style. The research method applied is library research by collecting literature-related data on factors influencing work enthusiasm. This study is descriptive, presenting findings narratively through various literature sources, including books, encyclopedias, scientific journals, newspapers, magazines, and documents. The results show that the level of work motivation, work intensity, work stress, work environment, compensation, and leadership style significantly influence work enthusiasm. High motivation tends to increase work productivity, while low motivation can hinder the level of employee productivity.